2012
DOI: 10.1122/1.4708601
|View full text |Cite
|
Sign up to set email alerts
|

Viscoelastic properties of solutions of polystyrene melts and carbon dioxide: Analysis of a transient shear rheology approach

Abstract: In this work, the viscoelastic, thermal and diffusion properties of solutions of polystyrene melts and carbon dioxide (CO 2) were analyzed using plate-plate rheometry in the transient mode. The objective of this study was to evaluate a transient shear rheology approach for high viscosity polymer melts, to verify superposition principles for polystyrene/CO 2 solutions and to measure the glass transition temperature as a function of pressure and CO 2 concentration. Two different procedures of saturating polystyr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 51 publications
0
17
0
Order By: Relevance
“…Typical values for b à are 10-50 GPa À1 for polymer melts [1,5,6,[30][31][32], 10-70 GPa À1 for lubricants [18,33] and 10-20 GPa À1 for mineral oils [34]. These values for b à are usually reported for the exponential law; however, they are also valid for small or medium pressure differences p à À p à ref .…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Typical values for b à are 10-50 GPa À1 for polymer melts [1,5,6,[30][31][32], 10-70 GPa À1 for lubricants [18,33] and 10-20 GPa À1 for mineral oils [34]. These values for b à are usually reported for the exponential law; however, they are also valid for small or medium pressure differences p à À p à ref .…”
Section: Introductionmentioning
confidence: 93%
“…However, the dependence of k à on p à is not clear and, surprisingly, experimental data for k à versus p à do not exist in the literature (at least as far as the author this work is aware). Handge and Altstadt [32] have suggested that if the time-temperature-pressure superposition principle is fulfilled, which appears to be the case for the polystyrene melts that they report on, then all relaxation times must scale with the same factor as the viscosity. In the present paper however k à is assumed to be constant; as shown in Ref.…”
Section: Introductionmentioning
confidence: 95%
“…Consequently, the regimes of glass transition and viscous flow appear at earlier times than for the pristine polymer phase. For amorphous polymers, this effect can be described by the time–temperature–pressure shift factor a T,p , i.e. in Eqns (1) and (2) the time t has to be replaced by t / a T,p for a sample which has been fully plasticised at time t = 0.…”
Section: Creep and Diffusion In Polymersmentioning
confidence: 99%
“…In principle, the local variation of concentration can be treated by a numerical analysis. In a pore–channel geometry, the solution for diffusion in a cylindrical hollow fibre can be applied in order to calculate the time of saturation, with κ=1true/ϵ0 and the initial porosity ϵ 0 of the membrane. Since the time for a complete saturation is infinity, the experimental saturation time is estimated by the time t 95 which corresponds to a saturation of 95% of the equilibrium value.…”
Section: Creep and Diffusion In Polymersmentioning
confidence: 99%
“…[43], the reduction of the transient shear viscosity and the plasticisation effect, respectively, in polystyrene melts caused by carbon dioxide was investigated. In general, homopolymers and blends of homopolymers have been studied more in depth compared to block copolymers.…”
Section: Introductionmentioning
confidence: 99%